Review: Martin Bittner (2008). Aufstand in den banlieues. Der Versuch einer Verbindung von Diskursanalyse und dokumentarischer Methode [Rebellion in the Banlieus: An Attempt to Combine Discourse Analysis and the Documentary Method] - Wischmann, Anke; Münte-Goussar, Stephan (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2008)
Martin BITTNER's "Rebellion in the Banlieus" analyses the 2005 protests in the French suburbs. BITTNER tries to localize the phenomena in educational and sociological research while developing an appropriate method to realize the project. The rebellion is described in its specific social and historical context and it becomes clear that it has to be understood as an event with a specific historical genesis that differs qualitatively from earlier rebellions in France. To analyse the rebellion as a public event, BITTNER focuses on three German weekly newspapers and a German perspective on the French rebellion becomes the main object. In his analysis, BITTNER develops a combination of the documentary method (BOHNSACK, 2007) and Foucauldian discourse-analysis (FOUCAULT, 2007). This combination is simultaneously developed and tested in the context of the three newspapers' varying perspectives on and assessments of the events in France.URN: urn:nbn:de:0114-fqs0901126